Responses Of Personal Agency Of Adolescents In Relation To The Covid 19 Pandemic Outbreak: An Exploratory Study With Children Of Mental Health Workers In Chile - Órdenes Velásquez, Andrea Nicole; Zamorano Díaz, Claudio Manuel (Journal of Neonatal Surgery, 2025)
During December 2019, cases of life-threatening pneumonia were reported in Wuhan, Hubei Province, China, naming it COVID-19. Due to its seriousness in terms of rapid spread and number of deaths, in March 2020 the World Health Organization (WHO) declared it a pandemic, presenting itself as a challenge for health systems. In the face of this crisis, different measures have been decreed globally to stop or reduce the spread of the virus, including distancing strategies and quarantines, which according to the results of research carried out would result in a negative impact on mental health for both the general population and children. girls and adolescents. In this scenario, the purpose of this research was to characterize the personal agency responses of adolescent subjects, children of mental health workers, in relation to the COVID-19 pandemic outbreak. For these purposes, the social constructionist perspective and a qualitative theoretical methodological approach from an exploratory design were considered as an epistemological basis. The interviews were conducted with 6 adolescents, this group being composed of men and women between the ages of 13 and 16 years. The collection of information was done through semi-structured interviews and the application of the adaptation of the narrative exercise "the comet of life", using the ZOOM platform. The analysis used was that of interpretive content, emerging data related to the responses of adolescents in 3 dimensions: pandemic and physical isolation, pandemic and family life, and pandemic and school life. This will contribute not only to the lives of these adolescents and their families but also to the reflection and knowledge of this situation so little studied.